The Effectiveness of Learning with the Team Based Project Method in the Decision Making Technique Course by Using the Product Oriented Module - Wijaya, Kinanti; Siregar, Syafiatun; Sutrisno; Yuzni, Siti Zulfa; Sari, Ruri Aditya; Idris, Iswandi; Ramadani (Lembaga Penelitian dan Pengabdian kepada Masyarakat, Universitas Negeri Jakarta, 2021)
The purpose of this study is (a) to identify learning using the team-based project method implemented in practical courses using product-oriented modules in vocational education. (b) to know the level of effectiveness of learning with the team-based project method implemented in practical courses using a product-oriented module in Vocational Education. This study used research related to this study, which were all students who were taking the Decision-Making Technique course. The number of research samples was 60 people (2 classes) of the 2018 Business Administration study program as a field test, 9 people as a small group test and 3 people for an individual test. The results showed that from the material expert, 4 aspects were assessed in the material expert test, namely the material aspect, the quiz question aspect, the linguistic aspect and the implementation aspect. The material aspect has a higher percentage value than the other three aspects, namely 85.45%, then the questions and quiz aspects and the implementation aspect have 80%, while the linguistic aspect has 60%. With this percentage value, the overall assessment of the material experts assesses that this learning media was considered